2009
DOI: 10.1161/strokeaha.108.531996
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Cerebral Autoregulation in Homozygous Sickle Cell Disease

Abstract: Background and Purpose-Sickle cell disease (SCD) is associated with cerebral hyperperfusion and an increased risk of stroke. Also, both recurrent microvascular obstruction and chronic hemolysis affect endothelial function, potentially interfering with systemic and cerebral blood flow control. We addressed the question whether cerebrovascular control in patients with SCD is affected and related to hemolysis. Methods-Systemic and cerebrovascular control were studied in 18 patients with SCD and 10 healthy subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 55 publications
(47 reference statements)
1
18
0
Order By: Relevance
“…14 In a previous study, we demonstrated that SCD patients also have an impaired dynamic cerebral autoregulation. 17 Together with the findings of the present study, these results imply that in SCD both mechanoregulation and chemoregulation as the 2 major operative mechanisms responsible for maintaining CBF are impaired, rendering SCD patients susceptible to ischemic episodes. Based on the highly sensitive control of the cerebral vasculature via changes in P ET CO 2 and the inverse relationship between CBF and ventilation, the alteration in CBF regulation has been proposed to contribute to breathing instability.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…14 In a previous study, we demonstrated that SCD patients also have an impaired dynamic cerebral autoregulation. 17 Together with the findings of the present study, these results imply that in SCD both mechanoregulation and chemoregulation as the 2 major operative mechanisms responsible for maintaining CBF are impaired, rendering SCD patients susceptible to ischemic episodes. Based on the highly sensitive control of the cerebral vasculature via changes in P ET CO 2 and the inverse relationship between CBF and ventilation, the alteration in CBF regulation has been proposed to contribute to breathing instability.…”
Section: Discussionsupporting
confidence: 85%
“…[14][15][16] Recently, we demonstrated that dynamic cerebral autoregulation is impaired in SCD. 17 Independent from cerebral autoregulation, the influence of the partial arterial carbon dioxide (CO 2 ) tension on CBF is of importance. Under normal conditions, increments and decrements of the partial arterial and thus end-tidal CO 2 tension (P ET CO 2 ) increase and decrease CBF by cerebral vasodilatation and vasoconstriction, respectively.…”
Section: ;114:3473-3478) Introductionmentioning
confidence: 99%
“…16 Exposure to hypoxia increased the mortality rate in a mouse model of sickle cell disease, 17 suggesting that these mice are susceptible to hypoxia-induced organ failure and death. In humans, adult sickle cell patients demonstrate impairment in cerebrovascular reserve (CVR) capacity 9 and autoregulation of CBF, 18 suggesting a deficiency in cerebrovascular reactivity in the brain of these patients. Elevated cerebral CBF and reduced CVR have also been reported in the pediatric population.…”
mentioning
confidence: 99%
“…However, adult patients with SCA exhibit impaired dynamic cerebral autoregulation when measuring middle cerebral artery velocity changes with postural changes. 25 Impaired cerebral autoregulation may directly contribute to small vessel ischemic disease and a decreased ability to buffer dramatic and sudden changes in blood pressure, placing patients at an increased risk for hemorrhagic stroke. 23 Patients who survive into adulthood with SCA are at risk for developing moyamoya vasculopathy, a progressive cerebrovascular vasoconstriction and development of small vessel collateral circulation.…”
Section: Neurologic Complications Of Sickle Cell Anemiamentioning
confidence: 99%